Developing a Community Education Roadmap for Society 5.0: A Mixed-Methods Study on Digital Literacy and Entrepreneurial Skills - Ansori Ansori; Tiffany Estherlita; Nandang Rukanda (Journal of Nonformal Education, 2026)
Background - The rapid development of technology in the Society 5.0 era demands transformative changes in community education to create a digitally inclusive and sustainable society. Research Urgency -  Existing community education systems still face gaps in preparing individuals to adapt to technological transformation. Therefore, structured strategies are needed to empower communities through digital literacy, entrepreneurial skills, and adaptive competencies. Research Objectives - This article explores the design and implementation of a roadmap for community education aimed at equipping individuals with digital literacy, entrepreneurial skills, and adaptive competencies. Research Method - The research employs a mixed-method approach, including surveys, focus group discussions, and case studies, to assess the needs and potential of communities. Research Findings - The findings highlight the critical role of digital infrastructure, capacity building for educators, and innovative learning models in fostering inclusive and effective education. The roadmap is structured into five phases: assessment, infrastructure development, capacity building, innovative learning implementation, and evaluation. This structured approach addresses existing gaps and provides actionable strategies to empower communities in embracing technological advancements. Research Conclusion - The results underline the importance of collaboration among stakeholders, including governments, private sectors, and local organizations, in ensuring the roadmap's success. Research Novelty/Contribution - Ultimately, the roadmap offers a strategic framework to prepare communities for the challenges and opportunities of Society 5.0, contributing to a more equitable and resilient society.